Desarrollo e implementación del modelo de madurez CMMI nivel 3 en la empresa Novacomp. - Bourrouett-Vásquez, Manuel (Instituto Tecnológico de Costa Rica, 2017)
The purpose of this document is to make known the way in which the development of the specialty practice project was carried out, which consisted in the implementation of the CMMI level 3 maturity standard in the company Servicios Computacionales Novacomp SA. Novacomp is a company dedicated to the development of out-tasking software and software factory, which has a philosophy of continuous improvement, so it is constantly looking for new ways to improve its processes and therefore its products. One of these ways was the decision to seek to achieve level 3 maturity in CMMI. Processes, documentation, interviews with Novacomp staff members, meetings, among other functions were reviewed, to gather enough inputs to start the project. After the initial analysis we proceeded with the elaboration of artifacts, policies, processes, among others, that are required by CMMI to comply with the standard. Finally, the CMMI-based work structure was implemented, which establishes the way in which the previously designed artifacts should be deployed, the ones responsible for their use and the benefits they will bring to the company concerning software development.
Informe final de práctica de especialidad (Bachillerato en Ingeniería en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2017.
Keywords: Desarrollo de software - Estandarización de procesos; Desarrollo de software - Procesos - Evaluación; Desarrollo de Software - Mejoramiento continuo